2005
DOI: 10.1103/physrevlett.95.055501
|View full text |Cite
|
Sign up to set email alerts
|

Global Minimum Determination of the Born-Oppenheimer Surface within Density Functional Theory

Abstract: We present a novel method, which we shall refer to as the dual minima hopping method (DMHM), that allows us to find the global minimum of the potential energy surface (PES) within density functional theory (DFT) for systems where a fast but less accurate calculation of the PES is possible. This method can rapidly find the ground state configuration of clusters and other complex systems with present day computer power by performing a systematic search. We apply the new method to silicon clusters. Even though th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
132
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 24 publications
4
132
0
1
Order By: Relevance
“…Si 16 Goedecker et al 8 showed that 16ttp-1 has the lowest energy whereas 16ss-1 is the second in the energy order on the basis of PWP-DFT calculations with the PBE functional. However, on basis of all-electron DFT calculations with both B3LYP and PBE1PBE hybrid functionals and the 6-311G ͑2d͒ basis set, we found that 16ss-1 is always lower in energy than 16ttp-1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Si 16 Goedecker et al 8 showed that 16ttp-1 has the lowest energy whereas 16ss-1 is the second in the energy order on the basis of PWP-DFT calculations with the PBE functional. However, on basis of all-electron DFT calculations with both B3LYP and PBE1PBE hybrid functionals and the 6-311G ͑2d͒ basis set, we found that 16ss-1 is always lower in energy than 16ttp-1.…”
Section: Resultsmentioning
confidence: 99%
“…The 16bilayer isomer was previously predicted to be the global minimum by Ho et al, 3 and its structure can be viewed as a network of eight parallel silicon dimers. The 16bilayer-1r, which was reported by Goedecker et al as the third lowestenergy isomer, 8 can be constructed by rotating three pairs of silicon dimers of 16bilayer-1 by 90°at the top. In addition, we display a cagelike isomer of Si 16 named 16cage-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the experimental evidence was immediately supported by calculations [32,[35][36][37]39,45,46]. In this work [47] we want study in detail the S-H phases with state of the art ab-initio material search minima hopping method (MHM) [48][49][50] and compute the superconducting properties with the completely parameter-free Density Functional Theory for Superconductors (SCDFT) [51]. At the same time we also extend the analysis to the Se-H system, predicting a fairly similar phase diagram and comparable superconducting properties.…”
mentioning
confidence: 95%
“…[1,2] Silicon clusters have been extensively investigated experimentally [3][4][5][6][7] and theoretically. [8][9][10][11][12][13][14][15] Contrary to the isolobal carbon, silicon favors sp 3 hybridization rather than sp 2 hybridization, which leads to rather asymmetric and reactive structures for pure silicon clusters and makes the formation of cage-like structures unstable. [16] One possible solution to overcome this deficiency is to add transition metal dopant atoms to the silicon clusters, which is known to induce the formation of stable and unreactive cage-like structures.…”
Section: Introductionmentioning
confidence: 99%